Geschlecht und Macht (feministische studien)

„When does a man become a monster?“ Odysseus’ fluide Identität in Jorge Rivera-Herrans’ EPIC – The Musical - Peine, Sara (Wasser Wesen Wandel. Fluidität in (mehr-als-)literarischen Medien)

Thermodynamic Properties of Tetramethoxysilane - Fiedler, F.; Baumhögger, Elmar; Kruse, Simon; Lemmon, E. W.; Kasper, Tina; Thol, M. (International Journal of Thermophysics)
Abstract A fundamental equation of state for tetramethoxysilane (TMOS) is developed based on the available experimental data. In addition, new density and speed of sound measurements were performed specifically for this work to improve the database. Owing to the limited overall data set, additional thermodynamic properties were analyzed to support the fitting procedure and ensure physically consistent behavior. Modified representations of thermodynamic properties that are typically employed in the fitting procedure were introduced to facilitate the application of constraints. The resulting model provides a consistent description of the thermodynamic properties of TMOS.

Vom Hühner-Holocaust über die Öko-Diktatur zum Kulturkampf um die Currywurst. Korpuslinguistische Perspektiven auf ernährungsbezogene Politisierungen - Markewitz, Friedrich; Wilk, Nicole M. (Zeitschrift für Literaturwissenschaft undLinguistik)

120 Tage im 'SS Experiment Love Camp'. Zu Genretropen und -kontroversen im Nazisploitationfilm - Markewitz, Friedrich (Pop-Zeitschrift)

Art the Clown goes to Hollywood. Wenn transgressives Genrekino Mainstream wird - Markewitz, Friedrich (Pop-Zeitschrift)

(Nicht)Nutzung von KI-Werkzeugen in der Lehre: ein Reflexionspapier - Rohlfing, Katharina J.; Steinhardt, Isabel; Scharlau, Ingrid; Schaper, Niclas; Holtfreter, Susan; Biere, Lea; Grimminger, Angela; Schmidt, Rebecca; Festner, Dagmar Franziska; Schmidt, Rebekka; Buhl, Heike M.; Mindt, Ilka; et al.

Intertwining theory and practice: Design of planning phases in PD training to support effective teacher planning processes - Knaudt, Katharina; Herold-Blasius, Raja; Selter, Christoph (Proceedings of the Fourteenth Congress of the European Society for Research in Mathematics Education (CERME14)

Fostering Knowledge Facets of the TPACK Framework Through Designing Digital Mathematical Escape Games – A Qualitative Content Analysis of Pre‑Service Teachers’ Self‑Reported Learnings and Challenges - Herold-Blasius, Raja; Gruhn, Katrin; Kleinschmidt, Vera; Thurm, Daniel; Tusche, Carina (International Journal of Science and Mathematics Education)

TPACK learning paths of pre-service teachers when designing digital mathematical escape games - Herold-Blasius, Raja; Kleinschmidt, Vera (Proceedings of the Nineteenth ERME Topic Conference: Connecting the Learning of Mathematics Teaching to Practice)

Digitale Escape Games in der Hochschullehre – Seminarkonzept - Herold-Blasius, Raja; Kleinschmidt, Vera

Defining Islamic Comparative Theology
Over the last decades, Comparative Theology has established itself in varying methodological ways while considering the reality and plurality of religions. Although Comparative Theology can be a confessional or a non-confessional endeavor, most protagonists and theorists have been Western Christians. This could lead to the conclusion that Comparative Theology is in fact a Christian undertaking and implicitly or explicitly bound to conceptions like Christology. Furthermore, it could be argued that there is a certain asymmetry of power in the discourse between religions when the parameters of Comparative Theology are defined mainly by Christian theologians. This volume aims to be the first step to programmatically and conceptionally explore the possibility of a genuinely Islamic Comparative Theology in a constructive endeavor. This endeavor should neither be misunderstood as an apologetic questioning of the status quo in Comparative Theology nor as a project that deconstructs Comparative Theology. Rather, by searching for new approaches from the Islamic traditions it opens up ways and forms of learning, hermeneutically complementary with prominent attitudes, methods in Comparative Theology.
Keywords: Comparative Theology; Islamic Theology; Islamic Comparative Theology

Chapter 5 Covenant Theology in the Qur’an—Challenges and Insights for Comparative Theology from a Muslim Perspective - Ghaffar, Zishan (Defining Islamic Comparative Theology)
Keywords: Covenant Theology; Qur'an; Comparative Theology; Islamic Comparative Theology

Empirische Studien zur Demokratiebildung im Lehramtsstudium in Nordrhein-Westfalen - Wehde, Janis

The Lord’s Prayer and its place in the London Underground. Reflections on religious diversity and a parody based on a central sacred text - Breckner, Anne (Religious Diversity and Global Concerns)

Informal approaches to predictive modeling: fostering data literacy and critical engagement through decision tree construction - Fleischer, Franz Yannik; Biehler, Rolf (ZDM – Mathematics Education)
Abstract This study investigates how secondary students construct and evaluate decision trees in an open exploratory task using CODAP. By analyzing students’ tree products and oral self-reports, we identified different data-based and context-based approaches to predictor selection and stopping criteria. Students engaged with key ideas of predictive modeling, including classification, model construction, accuracy, generalization, and interpretability. Informal exploration offered rich opportunities for subsequent teaching by enabling students to begin reconstructing central technical ideas and critical tensions of predictive modeling through diverse but meaningful reasoning approaches.

Unveiling Barriers to Recycling with a Focus on Design: An Ishikawa Diagram-Based Approach with Industrial Application - Rohde, Katharina; Gonzalez, Barbara Fernandez; Budde, Finn Lukas; Ott, Manuel; Mozgova, Iryna; Mendibe, Alain Alonso (Safe and Sustainable Value Creation by Design - Proceedings of the 21st Global Conference on Sustainable Manufacturing)
The circular economy offers decisive advantages over the currently prevalent linear economy in industry. Firstly, the reuse of products, individual parts and material reduces the need for new production or generation and the associated consumption of energy and resources. Secondly, it helps to avoid the generation of waste. Early consideration of circular economic principles in product development processes is essential to specifically promote reuse, reparability and recycling. Efficient recycling of assemblies requires well-defined strategies. However, various challenges hinder the efficiency of technical recycling processes in industrial applications. This paper presents an Ishikawa (fishbone) diagram-based approach to systematically identify and categorize these influences. The method is implemented within an industrial framework, highlighting key obstacles such as material composition, design constraints, use of technology, framework conditions, economic limitations and regulatory challenges. By applying a scenario analysis, this approach examines potential future developments and their impact on recycling-oriented design choices. This helps to identify critical influencing factors and supports the development of resilient and sustainable industrial practices. This framework will serve as the foundation for developing an automated approach to circular design, enabling industries to more effectively integrate sustainability into their processes and adapt to changing environmental demands.

Insights into an Iranian Internet Shutdown - Anonymous, Anonymous; Niere, Niklas; Graf Lange, Felix; Somorovsky, Juraj
In June 2025, Iran enacted a nationwide Internet shutdown, culminating its already strict censorship apparatus. While Internet shutdowns happen regularly, insights into these shutdowns are notoriously difficult to obtain: their timing is hard to predict, and measurements are often impossible. In this paper, we present unique measurements surrounding Iran’s 2025 Internet shutdown in June, which we acquired during a regular analysis of Iran’s censorship apparatus. We contextualize our findings of Iranian DNS, HTTP, TLS, and QUIC censorship during the shutdown with measurements from platforms such as Cloudflare Radar and user reports. Our measurements show that Iranian censorship changed before and after the shutdown, marking preparation and recovery periods. For instance, QUIC censorship went into effect before and stayed in effect after the shutdown, while DNS over TCP censorship was only present briefly before the shutdown and resumed working afterwards. We also measured general network instabilities, especially for UDP, after the shutdown and the disabling of certain middleboxes. Our findings indicate that the Iranian censor enforced its shutdown using fine-grained techniques instead of relying on an all-or-nothing blackout. We advertise for continued measurements of the Iranian censor and hypothesize that future shutdowns in censoring countries could be detected during their preparation phase.

Leveraging extreme-scale simulation data: a workflow framework for multidisciplinary simulator integration - Gräßler, Iris; Döhner, Niklas (Proceedings of the Design Society)
ABSTRACT: Engineers simulate system behavior to support decisions in product engineering. Leveraging such engineering simulation data in strategic product planning can support idea generation and early evaluation of design alternatives and limitations. However, limited resources and expertise hinder broader uptake in strategic product planning. This paper investigates simulator integration into automated workflows and key processing components to enable simulation without in-depth expertise. This approach improves strategic product planning by creating data-based decision support.
Keywords: simulation-based design; design tools; multi-/cross-/trans-disciplinary approaches; simulation data reuse

Conscious Artificial Intelligence in Service - Breidbach, Christoph; Lars-Erik, Casper Ferm; Maglio, Paul; Beverungen, Daniel; Wirtz, Jochen; Twigg, Alex (Journal of Service Management)
Purpose: The purpose of this study is to identify, analyze, and explain the implications that could arise for service settings if AI systems develop, or are perceived to develop, consciousness – the ability to acknowledge their own existence and the capacity for positive or negative experiences. Design/methodology/approach: This study proposes and explores four hypothetical scenarios in which conscious AI in service could manifest. We contextualize our resulting typology in the health service context and integrate extant literature on technology-enabled service, AI consciousness, and AI ethics into the narrative. Findings: This study provides a unique theoretical contribution to service research in the form of a Type IV theory. It enables future service researchers to apprehend, explain, and predict how functionally conscious AI in service might unfold. Originality: An increasingly prolific public discourse acknowledges that conscious AI systems may emerge. Against this backdrop, this study aims to systematically explore a question that is perhaps the most critical and timely, but also inherently speculative, in relation to AI in service research by introducing much-needed theory and terminology. Practical implications: The ethical use of conscious AI in service could emerge as a distinct competitive advantage in the future. Achieving this outcome involves speculative yet actionable recommendations that include training, guiding, and controlling how humans engage with such systems, developing appropriate wellbeing protocols for functionally conscious AI systems, and establishing AI rights and governance frameworks.
Keywords: AI; AI consciousness; AI ethics; service systems